On the magnetostructural transition in MnCoGeBx alloy ribbons - (:unkn) unknown (ELSEVIER SCIENCE SA, 2015)
The magnetostructural transition in the Mn0.96Co1.04GeB0.02 ribbon alloy was investigated. Chemical, structural, microstructural, and magnetic studies were performed on the samples which were annealed at different temperatures. The resulting samples underwent a first-order phase transition in which the characteristic structural transition temperature shows a near-linear and inversely proportional dependence to the annealing temperature. The magnetostructural transition occurs through a simultaneous ferroelastic-magnetic transition between the ferroelastic-paramagnetic and paraelastic-ferromagnetic phases. Our results suggest that the crystal structure of the hexagonal high temperature phase allows the formation of ferroelastic domains, and the domain walls act as the natural nucleation site of the low temperature paraelastic-ferromagnetic phase. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: MnCoGe system alloys; Melt-spun ribbons; Multiferroic; Magneto-structural transition; Ferroelastic domain walls; Nucleation; MARTENSITIC-TRANSFORMATION; PHASE-TRANSITIONS; TEMPERATURE